Analisis Kesiapan Implementasi Rekam Medis Elektronik Menggunakan Pendekatan DOQ-IT Di Klinik Pratama Wulandari Tahun 2025 - Daeli, Cosmas Samuel; Sitorus, Mei Sryendang; Hutasoit, Theresia; Sitompul, Osayku Inesa (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2026)
The implementation of Electronic Medical Records (EMR) is a mandatory requirement for all healthcare facilities in Indonesia to improve service quality, accelerate patient information access, and support data interoperability through a national platform. The purpose of this study was to analyze the readiness for the implementation of EMR using the DOQ-IT approach by assessing the influence of human resources, organizational work culture, governance and leadership, and IT infrastructure in healthcare services. This research used a descriptive quantitative method with total sampling of 16 respondents from various healthcare professions at Wulandari Primary Clinic. Data were collected using the DOQ-IT questionnaire consisting of multiple-choice questions. The analysis results showed that the overall assessment score was 74.44, which falls into Category II (fairly ready). This indicates that while there are strong capabilities in certain readiness components, weaknesses remain in others. Based on the four readiness aspects, only IT Infrastructure had the lowest classification score (2.50). The most prepared aspect was Human Resources (2.86), followed by Organizational Culture (2.67), and Governance and Leadership (2.58). Recomendation that need to be considered: Improve IT infrastructure, conduct regular training for staff, strengthen the role of leaders, conduct regular evaluations so that RME runs effectively